Lack of the normative lens: Discussions on research on micro‐targeted ads explanation of Facebook. Issue 1 (18th October 2019) - Ma, Yuanye
ABSTRACT : This paper observes that studies on the explanation of recommender systems lack a normative lens . Specifically, it uses Facebook's micro‐targeted advertisement explanations as a case for discussion, and shows how research mostly take a descriptive lens and focus on answering the what and how questions while the normative questions concerning how things should be are under explored. The paper argues that the normative and descriptive lenses are interdependent, and the lack of the normative lens contributes to inconsistent research suggestions. Explicitly putting on a normative lens is how researchers could avoid potential conflict among multiple normative goals.